Features of the modern process of patriotic upbringing by high school students in Ukraine. (Journal of Educational Sciences, 2016)
The article reveals the features of the modern process of Patriotic education of high school students. Features of the modern educational process: purposefulness, многофакторность, comprehensiveness, consistency, the hierarchy, consistency, continuity, self-controllability, poly orientation, availability, and integrity.Article includes the following sections:– Introduction;– features of the process of education;– Patriotic education;– organizational and pedagogical basis of Patriotic education;– the organization of a holistic educational process;– conclusion.This clearly demonstrates the use of the article the methodology of systematic and structured approach. At the same time, are the elements of the environmental approach. In the aspect of the humanization of Ukrainian system of education highlights the goals, objectives, content, andorganization of educational process, methods and forms of Patriotic education, its organizational structure. To the external factors of education traditionally attributed micro-, meso-, rules. The internal (subjective) factors affecting the Patriotic education of students, refer to the individual characteristics of the pupils, the level of competence of educators, the value orientation of participants in the educational process, a psychological climate in collective, style pedagogical leadership, but also the material conditions in which the process of upbringing patriotism Important assessment of the author is the preparatory stage of the educational process. There is great importance attached to the use diagnostic technologies. The object of diagnosis in the context of Patriotic education is the level of education of patriotism high school students, the level of readiness of teachers to carry out Patriotic education, conditions of Patriotic education as a pedagogical process. In order to prevent unwanted effects that may arise in the process of Patriotic education, is a forecast of the results of the patriotically-directed learning process, during which assesses the possible effectiveness of Patriotic education in these particular circumstances. Taking into account the results of diagnostics and forecasting of the project of organization of Patriotic education.
Keywords: patriotic upbringing; the purpose of patriotic upbringing; objectives; principles; methods and forms of organizational structure of the process of patriotic upbringing